2003
DOI: 10.1002/jcp.10377
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of thioredoxin reductase 1 regulates NF‐κB activation

Abstract: Thioredoxin reductase (TrxR) is a flavoprotein that contains a C-terminal penultimate selenocysteine (Sec) and has an ability to reduce thioredoxin (Trx), which regulates the activity of NF-kappa B. To date, three TrxR isozymes, TrxR1, TrxR2, and TrxR3, have been identified. In the present study, we found that among these isozymes only TrxR1 was induced by tumor necrosis factor-alpha (TNF alpha) in vascular endothelial cells. Furthermore, the overexpression of TrxR1 enhanced TNF alpha-induced DNA-binding activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 42 publications
1
45
0
Order By: Relevance
“…6,7) Among these three isozymes, TrxR1 is the most well characterized and is known to be inducible in response to various stimuli, including peroxynitrite, 8) phorbol ester, interleukin 1b, 9) and tumor necrosis factor a. 10) We have recently reported that cadmium also up-regulates the TrxR1 mRNA level in bovine arterial endothelial cells by activating NF-E2-related factor 2 (Nrf2), a stress-responsive transcriptional factor. 11) Nrf2 is activated by cadmium 12) and is shown to be involved in hemin-induced Trx gene expression 13) as well as TrxR1 gene expression.…”
mentioning
confidence: 99%
“…6,7) Among these three isozymes, TrxR1 is the most well characterized and is known to be inducible in response to various stimuli, including peroxynitrite, 8) phorbol ester, interleukin 1b, 9) and tumor necrosis factor a. 10) We have recently reported that cadmium also up-regulates the TrxR1 mRNA level in bovine arterial endothelial cells by activating NF-E2-related factor 2 (Nrf2), a stress-responsive transcriptional factor. 11) Nrf2 is activated by cadmium 12) and is shown to be involved in hemin-induced Trx gene expression 13) as well as TrxR1 gene expression.…”
mentioning
confidence: 99%
“…For instance, the proto-oncogene serine/threonine-protein kinase pim-1 (P11309) is predicted as one of the top five potential partners for each of the three thioredoxin related proteins TXN1_HUMAN, TXN5_HUMAN, TXNL_HU-MAN and the top potential partner for TXN1_HUMAN. While there is no direct evidence showing thioredoxin related proteins interact with Pim-1 kinase, recent research findings have revealed both proteins are regulated via the NF-kB pathway [38][39][40]. Another protein, mitogen-activated protein kinase 1 (P28482), is also predicted as a potential interacting candidate for TXNL_HUMAN which is consistent with its functional roles in signal transduction and apoptosis [41].…”
Section: Thioredoxin Related Proteinsmentioning
confidence: 71%
“…However, TrxR lost its synergistic action when the mutant Trx (32S/35S) replaced the wild-type Trx. To further confirm the role of TrxR, its selective inhibitor, goldthioglucose (Sakurai et al, 2004), was used to inhibit the activity of the endogenous TrxR. It was found that the resulted PPAR␣ activity increased as goldthioglucose concentration increased ( Figure 6C).…”
Section: Trx Inhibits Ppar␣ Transcriptional Activity In a Redox-depenmentioning
confidence: 98%